Radial Forearm Free Flap for Tongue Reconstruction - Sánchez Terán, Alfonso Iván; Fuertes-Muñoz, Anyely Nataly; Gutiérrez-Brambila, Martha Elena; Luna-García, Juan Carlos; Cervantes-Ruíz, Luis Anibal; Zúñiga-Vázquez, Luis Abraham; Chávez-Pérez, Gerardo (International Journal of Innovative Research in Medical Science, 2023)
A woman in his mid-50s presented with an ulcer on the right side of her tongue associated with sore throat. The lesion progressively grew until it became exophytic. An incisional biopsy showed a well-differentiated squamous cell carcinoma, invasive, ulcerated, p16 positive, with lymphovascular permeation and muscle infiltration so she was referred to a surgical oncologist. There was history of oral sex habits and poor dental hygiene. At physical examination there was a 2.5 x 2 cm neoformation on the right lateral side of the tongue associated with pain, which was mild, intermittent, and localized, the base of the tongue and floor of the mouth were apparently free. The team decided to perform a right hemiglossectomy plus radical neck dissection. Given the anatomical and functional needs of the area, a microvascular reconstruction with a Radial Forearm Free Flap was chosen due to its thinness, flexibility, ease of harvest, and reliability.